PEMUPUKAN GANDASIL-D TERHADAP PERTUMBUHAN BIBIT POHON PENGHASIL GAHARU JENIS Gyrinops versteegii (Gilg) Domke - Handiward Tonoro; Fabiola B. Saroinsong; Josephus I. Kalangi; Marthen T. Lasut (Universitas Sam Ratulangi, 2014)
ABSTRACTGaharu contains damar wangi from the mastic tree on a part of gaharu-producer trees that accurs naturally and have died due to a fungal infection that accurs naturally or artificially. The purpose of this study was to analyze the effect of frequency method Randomized Complete Design (CRD), with 5 treatment and 5 replications. A treatment without fertilizer, B treatment (application of fertilizer once a week, which is on Saturday, C treatment (twice a week, which are on Saturday and Tuesday, D treatment (3 times a week, which are on Saturday, Tuesday and thursday and E treatment (4 times a week, which are on Saturday, Monday, Wednesday, Friday. Planting medium used in this study is a mixture of soil, sand and chicken manure in the ratio 1:1:1 by volume. Variables measured were plant’s height, stem’s diameter and number of leaves. The results showed that the application of leaf fertilizer Gandasil D on Gyrinops versteegi seedi deliver tangible results in plants height. D treatment (application of fertilizer 3 times a week) showed good results in plant compared with other treatment.Keywords : Gyrinops caudata, Agarwood, foliar fertilizer Gandasil D